Understanding the impact of sand extraction on benthic ecosystem functioning: a combination of functional indices and biological trait analysis - Goedefroo, Nanou; Braeckman, Ulrike; Hostens, Kris; Vanaverbeke, Jan; Moens, Tom; De Backer, Annelies (Frontiers in Marine Science, 2023)
Marine aggregates have been intensively extracted in the North-East Atlantic over the past decades. This study aimed to assess the effect of sand extraction on benthic ecosystem functioning using a combination of biological traits and functional indices (the bioturbation (BPc) and irrigation potential (IPc) and secondary production (SPc) of the macrobenthic community). Data on macrobenthos, sediment properties and extraction intensity were collected over a time period of ten years (2010 – 2019) for three coarse sediment extraction areas in the Belgian Part of the North Sea, each with a different extraction regime. Sediment parameters such as the medium sand fraction (250 – 500 µm) and median grain size showed a significant effect on all functional indices. Whilst sand extraction variables only significantly affected secondary production estimates. The secondary production of the macrobenthic community decreased following a high yearly extraction intensity, whereas a high cumulative (10-year period) extraction intensity resulted in a slightly increased secondary production. Species-specific responses revealed that these high cumulative extraction volumes increased the abundance of opportunistic species, which could have contributed to the higher SPc values observed in cumulative disturbed areas. Response traits such as tube-living and sessile individuals with a pelagic egg development were positively influenced by a long-term disturbance, an indication of a more disturbance-tolerant community. A short-term disturbance rather seemed to favor a macrobenthic community characterized by a higher burrowing capability. In terms of effect traits, both short- and long-term extraction clearly favored deposit feeders, which can structure organic matter distribution and thus indirectly influence nutrient and oxygen fluxes as well. Future in situ measurements in sand extraction areas could help to unravel and strengthen our understanding of the ecosystem processes linked to these trait-based observations.